Facile Doping and Work‐Function Modification of Few‐Layer Graphene Using Molecular Oxidants and Reductants. (3rd January 2017) - Mansour, Ahmed E.; Said, Marcel M.; Dey, Sukumar; Hu, Hanlin; Zhang, Siyuan; Munir, Rahim; Zhang, Yadong; Moudgil, Karttikay; Barlow, Stephen; Marder, Seth R.; Amassian, Aram
Abstract : Doping of graphene is a viable route toward enhancing its electrical conductivity and modulating its work function for a wide range of technological applications. In this work, the authors demonstrate facile, solution‐based, noncovalent surface doping of few‐layer graphene (FLG) using a series of molecular metal‐organic and organic species of varying n‐ and p‐type doping strengths. In doing so, the authors tune the electronic, optical, and transport properties of FLG. The authors modulate the work function of graphene over a range of 2.4 eV (from 2.9 to 5.3 eV)—unprecedented for solution‐based doping—via surface electron transfer. A substantial improvement of the conductivity of FLG is attributed to increasing carrier density, slightly offset by a minor reduction of mobility via Coulomb scattering. The mobility of single layer graphene has been reported to decrease significantly more via similar surface doping than FLG, which has the ability to screen buried layers. The dopant dosage influences the properties of FLG and reveals an optimal window of dopant coverage for the best transport properties, wherein dopant molecules aggregate into small and isolated clusters on the surface of FLG. This study shows how soluble molecular dopants can easily and effectively tune the work function and improve the optoelectronic properties of graphene. Abstract : Solution‐based noncovalent doping of few‐layer graphene using novel metal‐organic and organic molecules is demonstrated to enhance the conductivity and modulate the work function over a range of 2.4 eV with marginal reduction of mobility. The effects of dopant strength and coverage are shown to play a crucial role in the optimization of the performance of few‐layer graphene as a transparent conductive electrode.